Dietary glycerin does not affect meat quality of Ile de France lambs - Borghi, Thiago Henrique [UNESP] (2016)
The objective of this study was to evaluate the physicochemical and nutritional characteristics of meat from three muscles of Ile de France lambs fed diets containing different levels of glycerin as an alternative to corn. Thirty non-castrated feedlot Ile de France lambs weighing 15 +/- 0.2 kg were housed in individual pens and slaughtered at 32 +/- 0.2 kg. Treatments consisted of three diets: sugarcane + 0% glycerin; sugarcane + 10% glycerin; and sugarcane + 20% glycerin; and three muscles were evaluated: triceps brachii, semimembranosus, and longissimus lumborum. No interactions were observed among glycerin levels and muscle types for the quality characteristics evaluated. Muscles were similar in terms of physicochemical and nutritional characteristics, and only differed in sarcomere length, diameter of muscle fibers, and cholesterol content. Dietary glycerin did not affect pH, water holding capacity (24 h and 30 days after slaughter), weight loss by thawing and cooking, shear force, diameter of muscle fibers, sarcomere length, lipid oxidation, chemical composition, or meat cholesterol content. Dietary glycerin resulted in a linear decrease of muscle yellowness from 3.99 to 3.29. Dietary glycerin altered intramuscular fat fatty acid profile, increasing the concentration of margaric acid (1.47 to 2.61%). Up to 20% glycerin can be included in the diet of feedlot lambs without any harm to meat quality.